Adsorption, leaching and bioavailability of cadimum and lead in aqueous solution and contaminated soils amended with modified biochar - Fahmi, Alaa Hasan (2018)
Cadmium (Cd) and lead (Pb) are among the global priority pollutants and contaminations of these heavy metals cover a wide range of soils. Biochar has been proven to be a very good adsorbent of heavy metals. Reduction of its particle size may increase the sorption and removal of heavy metals from soils or aqueous solution. The present study investigated the effects of crushing oil palm empty fruit bunch biochar (EFBB) to different particle sizes on the adsorptive removal of Cd and Pb from aqueous solution, extractable, leaching and phytoavailability of Cd and Pb in contaminated soil. Three different particle sizes of EFBB were used in this study; coarse (C-EFBB) (>2 mm), medium (M-EFBB) – (0.25 ‒ 0.5 mm) and fine (F-EFBB) (< 0.05 mm). The F-EFBB was also coated with Fe to produce an iron coated F-EFBB (ICF-EFBB). A commercially available activated carbon (AC) was also included in the study as a benchmark for the sorption properties of the modified biochars. All the adsorbents were characterized for their physico-chemical and morphological properties using standard methods. A batch equilibrium study was performed using 0.1 g of each adsorbent with 40 mL of solution containing 0 ‒ 500 mg L−¹ Cd and/or Pb. The isotherm data was fitted to Freundlich and Langmuir’s sorption isotherm models. The C-EFBB and F-EFBB at three different rates (0%, 0.5% and 1%) were added to soils contaminated with Cd and/or Pb and the extractable, leaching and phytoavailability of these two metals were studied.